Support for regulation versus compliance: Face masks during COVID-19 - Dohyeong Kim; Richard T. Carson; Dale Whittington; Michael Hanemann (Elsevier, 2023)
Objectives: Wearing masks could still be one of the few non-pharmaceutical interventions for controlling the pandemic. There are people who wear them and people who don't, but this framing is overly simplistic. We aim to chart the contradictions in attitudes and behavior regarding mask wearing and describe the messaging challenge that these generate. Study design: Our data come from a survey administered to a nationally representative sample of 2000 respondents from the YouGov panel of US households in August-September 2020. Methods: Respondents were asked whether they wear a facemask when they go outside their home since the COVID-19 epidemic began and whether they support or oppose your municipal government passing mask wearing regulation. We also collected respondents' demographic and economic characteristics, knowledge regarding the facts of COVID-19 and political ideology. Results: A substantial majority of Americans (60%) both favor a masking requirement and are themselves wearing masks, while 13% oppose a mask mandate and do not wear masks. In contrast, 17% of Americans oppose a mask mandate but are currently wearing one, while 10% do not wear a mask but favor a mask mandate. These two groups are distinctively different from one another and the other groups in their socioeconomic characteristics, risk perception and political beliefs. Conclusions: Our study offers a better understanding of the mismatch between mask wearing behavior and attitude toward the mask mandate, which will help the public health authorities to devise policies regarding mask wearing as an effective intervention to manage the pandemic.